PENGARUH PENERAPAN MODEL COURSE RIVEW HORAY TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SD - Ratna Sari, Mira Dwi; Sugiyono, Sugiyono; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to analysis the effect of applying the model cooperative type course riview horay in students’ social science learning achievement on year-4 of Elementary School 56 Pontianak Barat. The method this research is experiment with the research form of quasi experimental design, with nonequivalent control gruop design. The population of this research was all of Year-4 students of Elementary School 56 Pontianak Barat. The sampel of this research specified with technique purposive sampling consist of 33 students in class IV B as control class and 33 students in class IVC as experiment class. The researcher collected the data by the measurement technique in using paper test have multiple choice form numbering 50 question. Based on count obtained an average of achievement post-test control class 61,18 and the average of achievement post-test experimental class 71,00 thus obtained tcount post-test data of 4,741 with ttable for α =5% and df = 64 that mean 1,998, there were tcount > ttable so Ha was accepted. The effect size was categorized as medium effect since the ES value was 0,62. In conclusions, the effect of applying the model cooperative type course riview horay model is significant and effective for students’ social science learning achievement on year-4 of Elementary School 56 Pontianak Barat. Key words: The effect, cooperative type course riview horay, achievement, social science.